Loosening of environmental licensing threatens Brazilian biodiversity and sustainability - Ruaro, Renata; Zaia Alves, Gustavo H.; Tonella, Lívia; Ferrante, Lucas; Fearnside, Philip M. (DIE ERDE – Journal of the Geographical Society of Berlin, 2022)
Environmental licensing is one of Brazil’s main environmental-policy instruments and is intended to regulate anthropogenic activities and to avoid their impacts on the environment. This licensing is now at risk to being annihilated. Bill 3729/2004 was recently approved by Brazil’s Chamber of Deputies, and if approved by the Senate (as is likely) it would create the so-called ‘general law of environmental licensing’ and a series of changes weakening environmental impact assessments, public participation and supervision by environmental agencies. The changes include creation of a self-declared license in which licenses would be issued automatically without any analysis by technical staff in the environmental agencies. Various types of small and medium-sized projects would be completely exempted from licensing. If approved, the bill would cause irreversible environmental losses to megadiverse Brazilian ecosystems and allow installation of projects with high environmental impact without any impact analysis or measures to minimize or recover from impacts or to provide environmental compensation for them.